Pemberdayaan Ekonomi Masyarakat oleh Pengusaha - Maudi Nurhadiasari; Agus Ahmad Safei; Dedi Herdiana (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
This study aims to determine the work steps, obstacles and results of Community Economic Empowerment in PD. Ar-Rahmah. This study uses a qualitative approach with the method used is descriptive method. The results of the study show the work steps for empowering the community's economy carried out by PD. Ar-Rahmah, namely by providing motivation to work and providing directions for work steps to be more independent, as well as providing many new innovations for the progress of the PD tea leaf factory. Ar-Rahmah. Opening employment opportunities, and holding such as a savings and loan cooperative system without interest, and how to pay in salary deductions, or in installments, or due to obstacles Obstacles in empowering the community's economy at PD Ar-Rahmah, namely from an internal and external perspective and the results of the empowerment community economy in PD. Ar-Rahmah is quite well felt by employees and the surrounding community. With the existence of jobs around the place of residence it is not difficult for the community to have to migrate and leave their families